Obstructive sleep apnea syndrome in polycystic ovary syndrome: a systematic review and meta-analysis - Abdul Jafar, Nur K.; Al Balushi, Afra; Subramanian, Anuradhaa; Lee, Siang Ing; Bennett, Christie J.; Moran, Lisa J.; Mousa, Aya; Tay, Chau Thien; Teede, Helena J.; Mansfield, Darren R. (Frontiers in Endocrinology, 2025)
BackgroundPolycystic ovary syndrome (PCOS) has been associated with a high prevalence of obstructive sleep apnea syndrome (OSAS). However, the impact of OSAS on the PCOS symptom profile remains unclear. This systematic review and meta-analysis, which informed the 2023 International Evidence-based PCOS Guideline, aims to assess the prevalence and related symptoms of OSAS among females with and without PCOS.MethodsA systematic search using databases (MEDLINE, Embase, EBM Reviews, PsycInfo and CINAHL) was performed until 16th May 2024. Random-effects restricted maximum likelihood meta-analyses compared OSAS and related symptoms between PCOS and non-PCOS groups. OSAS outcomes were categorized as apnea-hypopnea index (AHI)≥5 only, AHI≥5 with symptoms, AHI≥10 with symptoms and composite OSA (i.e., all AHI cut-offs with and/or without symptoms). Subgroup analyses by body mass index (BMI), age, PCOS diagnostic criteria and ethnicity were performed. Risk of bias and certainty of evidence by the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) framework were conducted.ResultsFrom 4438 records, 3205 titles/abstracts were screened and 40 were eligible for full-text screening. Eight cross-sectional studies met inclusion criteria and meta-analysis. The pooled prevalence of OSA was 37.0% in PCOS (29.0% adolescents; 40.0% adults) and 6.0% in non-PCOS. Compared with non-PCOS, those with PCOS showed higher risk for composite OSA (odds ratio (OR): 9.52; 95% CI: 3.90 to 23.26; I2 = 54.5%; 8 studies, n=942; P<0.001) and more pronounced OSAS risk with increasing symptom severity in PCOS (AHI≥5 OR: 3.90; 95% CI: 1.63 to 9.34; AHI≥5 with symptoms OR: 17.95; 95% CI: 6.17 to 52.22; AHI≥10 with symptoms OR: 30.61; 95% CI: 7.99 to 117.25, all P ≤ 0.0023). Subgroup results showed significantly higher risk of OSAS overall in overweight/obesity, adults and white ethnicity compared with normal weight, adolescent and Asian subgroups, respectively (all P<0.001), but independent of PCOS diagnostic criteria.ConclusionThe prevalence of OSA was higher in PCOS compared with non-PCOS groups, with the risk of OSAS increasing with worse symptom severity. Adults and those of higher BMI and of white ethnicity were at increased risk of OSAS. Hence, identifying and treating OSAS symptoms in PCOS may be beneficial, but further validation of findings is warranted.